Proposed Business Strategy of Indihome a Division of PT. Telekomunikasi Indonesia (TELKOM) - Ricky Febrian, Muhammad; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2016)
Abstract. Many companies in Indonesia telecommunications industry require significant corporate strategy development in order to face the high competition in the market. To compete in a dynamic business area, companies in this industry need to develop an effective strategy. The executives must design and implement strategies that fit the needs of the market. In addition, the company is required to seek opportunities to deal with those changes. PT Telkom Indonesia, which is the leader in the telecommunication industry in Indonesia has been preparing a strategy to address industry trends and market changes. PT Telkom with 164 products divided into TIMES (Telecommunication, Information, Media, Edutainment and Services) categories has different maturity level of products with diversified business challenges as well. In 2015, PT Telkom provided an innovative product to customers namely triple play services (3P), which were fix line, internet and internet TV services bundled in one product, Indihome. Unfortunately Indihome was not able to meet the customer needs for data service, characterized by Indihome service penetration targets’ being not achieved in the third trimester. Based on Indihome Market Penetration Data, it appears that the achievement of Indihome service was not maximized, and many operational division found it hard to achieve the target and also face the churn issue.  Besides, looking from the market share perspective, the market share of PT Telkom in broadband industry is constantly decreasing. It is calculated that PT Telkom has the revenue market share with around 64,23% which falls by 9% from the previous years. Because of that PT Telkom should evaluate their business strategy in order to maintain their position as the market leader. Based on such issues, there is a need of analyzing and exploring the internal & external factor that affect the Indihome business and furthermore propose the business strategy suitable with the current condition. This problem can be solved by analyzing both internal and external factors to identify opportunities and threats of the industry as well as the strengths and weaknesses of the company. The tools used to analyze external environment is the general analysis, industry environtment analysis and competitor analysis. The tools used to analyze internal environment is resources, capabilities, core competencies and value chain of the company. This final project focus on determining the company's strategy and implementation process. Internal and external analysis results are used to determine where the company's position in the industry by performing calculations of EFAS and IFAS. Based on directional matrix, the company’s position is in the growth strategy, then the strategies chosen are vertical and horizontal strategy. The business strategy that suitable for Indihome industry is integrated cost leadership & differentiation, supported by eight alternative strategies to support its functional strategy derived from the TOWS Matrix which are market expansion, such as, new product development, build customer satisfaction, maximize existing infrastructure, continous improvement, maximize online media, increase level of productivity and provide new business model. The key performance indicator for PT Telkom especially for Indihome product was made as guidance step to achieve company objective and function level program.   Keywords : Business Level Strategy, Telecommunication Service, Business Formulation